![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(x^2-6x+10>x^2-6x+9=\left(x-3\right)^2>0\\ \Rightarrow x^2-6x+10>0\)
b)\(4x^2-20x+27>4x^2-20x+25=\left(2x+5\right)^2\ge0\\ \Rightarrow4x^2-20x+27>0\)
c)\(x^2+x+1>x^2\ge0\)
d)\(x^2+4x+y^2+6y+15=\left(x+2\right)^2+\left(y+3\right)^2+2\\ \left(x+2\right)^2\ge0;\left(y+3\right)^2\ge0;\\ \Rightarrow x^2+4x+y^2+6y+15\ge2>0\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Ta có :\(\frac{x}{4y+z}=\frac{y}{4z+x}=\frac{z}{4x+y}=\frac{x+y+z}{4y+z+4z+x+4x+y}=\frac{x+y+z}{5\left(x+y+z\right)}=\frac{1}{5}\)
=> \(\hept{\begin{cases}\frac{x}{4y+z}=\frac{1}{5}\\\frac{y}{4z+x}=\frac{1}{5}\end{cases}}\Rightarrow\hept{\begin{cases}\frac{x}{4y+z}=\frac{1}{5}\\\frac{4z+x}{y}=5\end{cases}}\)
Khi đó A = 2019 - 1/5 + 5 = 2023,8
\(\frac{x}{4y+z}=\frac{y}{4z+x}=\frac{z}{4x+y}=\frac{x+y+z}{4y+z+4z+x+4x+y}=\frac{x+y+z}{5\left(x+y+z\right)}=\frac{1}{5}\)
\(\Rightarrow\hept{\begin{cases}\frac{x}{4y+z}=\frac{1}{5}\\\frac{y}{4z+x}=\frac{1}{5}\end{cases}\Rightarrow\hept{\begin{cases}\frac{x}{4y+z}=\frac{1}{5}\\\frac{4z+x}{y}=5\end{cases}}}\)
Khi đó \(A=2019-\frac{1}{5}+5=2013,8\)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a ) \(x^2+4x+5=x^2+2.x.2+2^2+1=\left(x+2\right)^2+1\)
\(Do\left(x+2\right)^2\ge0\Rightarrow\left(x+2\right)^2+1\ge1>0\forall x\left(đpcm\right)\)
b) \(x^2-x+1=\left(x-\frac{1}{2}\right)^2+\frac{3}{4}\)
\(Do\left(x-\frac{1}{2}\right)^2\ge0\Rightarrow\left(x-\frac{1}{2}\right)^2+\frac{3}{4}\ge\frac{3}{4}>0\forall x\left(đpcm\right)\)
c)\(-\left(4x^2-12x+9\right)-1=-\left(2x-3\right)^2-1\)
\(Do-\left(2x-3\right)\le0\Rightarrow-\left(2x-3\right)-1\le-1\forall x\)
\(x^2+2.x.2+2^2+5-4\) \(\Rightarrow\left(x+2\right)^2+5-4\) \(\Rightarrow\left(x+2\right)^2+1\)
vì \(\left(x+2\right)^2\ge0\) \(\Rightarrow\left(x+2\right)^2+1\ge1\) \(\ge0\) \(\Rightarrow dpcm\)
b) \(x^2-2.x.\frac{1}{2}+\left(\frac{1}{2}\right)^2+1-\left(\frac{1}{2}\right)^2\) \(\Rightarrow\left(x-\frac{1}{2}\right)^2+\frac{5}{4}\)
vì \(\left(x+\frac{1}{2}\right)^2\ge0\) \(\Rightarrow\left(x+\frac{1}{2}\right)^2+\frac{5}{4}\ge\frac{5}{4}\ge0\) \(\Rightarrow dpcm\)
c) \(12x-4x^2-10=-\left(4x^2-12x+10\right)\) = \(\left[\left(2x\right)^2-2.2x.3+3^2\right]+10-3^2\)
\(\Rightarrow\left(2x-3\right)^2+10-9\) \(\Rightarrow\left(2x-3\right)^2+1\) vì \(\left(2x-3\right)^2\ge0\Rightarrow\left(2x-3\right)^2+1\ge1hay\ge0\left(1>0\right)\Rightarrow dpcm\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Để 4x(x - 3) > 0
Th1 : \(\hept{\begin{cases}4x>0\\x-3>0\end{cases}\Rightarrow\hept{\begin{cases}x>0\\x>3\end{cases}\Rightarrow}x>3}\)
Th2 : \(\hept{\begin{cases}4x< 0\\x-3< 0\end{cases}\Rightarrow\hept{\begin{cases}x< 0\\x< 3\end{cases}\Rightarrow}x< 3}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(x^2+4x>0\Leftrightarrow x\left(x+4\right)>0\) <=> x và x+4 cùng dấu
\(\left(+\right)x>0;x+4>0\Rightarrow x>0;x>-4\Rightarrow x>0\)
\(\left(+\right)x< 0;x+4< 0\Rightarrow x< 0;x< -4\Rightarrow x< -4\)
Vậy x>0 hoặc x<-4 thì.................
\(x^2+4x>0\Leftrightarrow x\left(x+4\right)>0\)
\(\Leftrightarrow\orbr{\begin{cases}x>0\\x+4>0\end{cases}\Leftrightarrow\orbr{\begin{cases}x>0\\x>-4\end{cases}\Leftrightarrow}x>0}\)
\(\Leftrightarrow\orbr{\begin{cases}x< 0\\x+4< 0\end{cases}\Leftrightarrow\orbr{\begin{cases}x< 0\\x< -4\end{cases}\Leftrightarrow}x< -4}\)
vậy...........
Bài làm:
Ta có: \(x^2+4x>0\)
\(\Leftrightarrow x\left(x+4\right)>0\)
Ta thấy \(x< x+4\) nên => \(\orbr{\begin{cases}x>0\\x+4< 0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x>0\\x< -4\end{cases}}\)
Vậy \(x>0\) hoặc \(x< -4\)